DAMPAK PERDAGANGAN INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI: INDONESIA DAN VIETNAM - Indah Khairunnisa Sihotang; Nanda Syafira Afriyani; Riska Amaliah; Suhardina, Suhardina; Dwita Sakuntala (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to compare the impact of international trade on the economic growth of Indonesia and Vietnam in the period 2021-2023. The research method used is qualitative with library research, which uses books, journals, and previous research, as sources of information. The results of the research on the impact of international trade on the economic growth of the two countries reflect different challenges and opportunities. Indonesia has successfully capitalized on the momentum of the global recovery to strengthen its trade position, while Vietnam needs to face the challenge of maintaining the stability of trade’s contribution to GDP. These differences highlight the importance of responsive and innovative trade policies in the face of a changing global economic environment.